Long-Term Outcomes in Children with Steroid-Resistant Nephrotic Syndrome Treated with Calcineurin Inhibitors - Beins, Nathan T.; Dell, Katherine M. (Frontiers in Pediatrics, 2015)
Background: Steroid resistant nephrotic syndrome (SRNS) is an important cause of chronic kidney disease (CKD) in children that often progresses to end-stage renal disease (ESRD). Calcineurin inhibitors (CNIs) have been shown to be effective in inducing short-term remission in some patients with SRNS. However, there are little data examining their long-term impact on ESRD progression rates. Methods: We performed a retrospective chart review of all patients treated for SRNS with CNIs at our institution from 1995-2013. Data collected including demographics, initial response to medical therapy, number of relapses, progression to ESRD, and treatment complications. Results: A total of 16 patients met inclusion criteria with a mean follow-up of 6.6 years (range 0.6-17.6 years). Histopathological diagnoses were focal segmental glomerulosclerosis (8), mesangial proliferative glomerulonephritis (4), IgM nephropathy (3), and minimal change disease (1). Three patients (18.8%) were unresponsive to CNIs while the remaining 13 (81.2%) achieved remission with CNI therapy. Six patients (37.5%) progressed to ESRD during the study period, three of whom did so after initially responding to CNI therapy. Renal survival rates were 87%, 71%, and 57% at 2 years, 5 years, and 10 years respectively. Non-Caucasian ethnicity was associated with progression to ESRD. Finally, a higher number of acute kidney injury episodes was associated with a lower final estimated glomerular filtration rate. Discussion: Despite the majority of SRNS patients initially responding to CNI therapy, a significant percentage still progressed to ESRD despite achieving short-term remission. Recurrent episodes of AKI may be associated with progression of CKD in SRNS patients with.